Current studies of aspirin as an anticancer agent and strategies to strengthen its therapeutic application in cancer - Tran, Phuong H.L.; Lee, Beom Jin; Tran, Thao T.D. (Current Pharmaceutical Design, 2021)
Aspirin has emerged as a promising intervention in cancer in the past decade. However, there are ex-isting controversies regarding the anticancer properties of aspirin as its mechanism of action has not been clear-ly defined. In addition, the risk of bleeding in the gastrointestinal tract from aspirin is another consideration that requires medical and pharmaceutical scientists to work together to develop more potent and safe aspirin therapy in cancer. This review presents the most recent studies of aspirin with regard to its role in cancer prevention and treatment demonstrated by highlighted clinical trials, mechanisms of action as well as approaches to develop aspirin therapy best beneficial to cancer patients. Hence, this review provides readers with an overview of aspirin research in cancer that covers not only the unique features of aspirin, which differentiate aspirin from other non-steroidal anti-inflammatory drugs (NSAIDs), but also strategies that can be used in the development of drug delivery systems carrying aspirin for cancer management. These studies convey optimistic messages on the continuing efforts of the scientist on the way of developing an effective therapy for patients with a low response to current cancer treatments.
Keywords: Anti-Inflammatory Agents, Non-Steroidal; Antineoplastic Agents; Aspirin; Hemorrhage; Humans; Neoplasms; Aspirin; Cancer; Drug delivery systems; Mechanism of action; Prevention; Treatment